The Influence of The Relationship Marketing, Influencer Marketing and Features on Purchasing Decisions in Zalora E-Commerce Users in Badung Regency - Ni Komang Trisnayati Utami; Ida Ayu Putu Widani Sugianingrat; I Komang Gede (Management and Applied Social Studies Review, 2023)
Purpose - Consumers before making a purchase will do a lot of evaluation by looking at the considerations that exist because there are indeed many factors that must be considered by consumers, so that the products purchased are really in accordance with their wants and needs. Because there are many factors that influence consumer purchasing decisions, including relationship marketing, influencer marketing and features. The formulation of the problem and the purpose of this research is to find out how the influence of relationship marketing, influencer marketing and features on purchasing decisions. Methodology – The location of this research was in Badung Regency and the sample used was 95 respondents. Research method used is quantitative. In this study the data analysis technique used is the Classical Assumption, Multiple Linear Regression, Coefficient of Determination, t test and F test Findings - Based on the results of the study, it can be seen that relationship marketing has a significant positive influence on purchasing decisions, influencer marketing has a significant positive influence on purchasing decisions, features has a significant positive influence on purchasing decisions and simultaneously relationship marketing , influencer marketing and features has a positive and significant influence on purchasing decisions. The magnitude of the influence of the independent variable on purchasing decisions is 53%. Originality – Application of relationship marketing, influencer marketing, and features on zalora e-commerce to purchasing decisions.